Unique challenges of cystic fibrosis‐related diabetes. Issue 9 (10th May 2018) - Bridges, N.; Rowe, R.; Holt, R. I. G.
Abstract: Individuals with cystic fibrosis and pancreatic insufficiency have a gradual decline in insulin secretion over time, which results in an increase in the prevalence of diabetes with age; up to 50% of adults with cystic fibrosis aged over 35 years have diabetes. Cystic fibrosis‐related diabetes differs from Type 1 and Type 2 diabetes in several ways; there is a pattern of insulin deficiency with reduced and delayed insulin response to carbohydrates but a sparing of basal insulin that results in glucose abnormalities, which are frequently characterized by normal fasting glucose and postprandial hyperglycaemia. Insulin deficiency and hyperglycaemia, even at levels which do not reach the threshold for a diagnosis of diabetes, have an adverse impact on lung function and clinical status in people with cystic fibrosis. Although the risk of microvascular complications occurs as in other forms of diabetes, the main reason for treatment is to prevent deterioration in lung function and weight loss; treatment may therefore be required at an earlier stage than for other types of diabetes. Treatment is usually with insulin, but management needs to take into account all the other medical issues that arise in cystic fibrosis. What's new?: Cystic fibrosis‐related diabetes (CFRD) is distinct from Type 1 and Type 2 diabetes. CFRD and impaired glucose tolerance have an adverse effect on clinical status in cystic fibrosis (CF), and treatment of CFRD is primarily aimed at reducing this impact. Treatment may be required at an earlier stage than for other types of diabetes to prevent deterioration of lung function and weight loss. The treatment of choice is insulin but should take account of other medical issues in CF.